The Role of Solidarity Economy in Enhancing Community Resilience After Social Crisis - Petro Borysko (Kampret Journal, 2026)
This study examines the role of the solidarity economy in increasing community resilience after a social crisis. Social crises, such as economic downturns and pandemics, often lead to economic instability, social fragmentation, and increased vulnerability within communities. This research aims to analyze how these practices contribute to resilience, identify the mechanisms involved, and evaluate their overall effectiveness. The study adopts a mixed-methods approach, combining qualitative and quantitative techniques. Data were collected through in-depth interviews, questionnaires, observations, and documentation within a selected community affected by a social crisis. The data were analyzed using thematic analysis for qualitative insights and descriptive statistics for quantitative findings. The results indicate that the solidarity economy plays a significant role in enhancing community resilience by strengthening social cohesion, providing economic support, fostering adaptability, and promoting participatory decision-making. However, the study also identifies several challenges, including sustainability issues, limited capital, weak management, and policy constraints, which may hinder the long-term effectiveness of solidarity-based initiatives. The findings further reveal that the success of the solidarity economy is influenced by internal factors such as community participation and leadership, as well as external factors including government support and access to resources. In conclusion, the solidarity economy serves as a viable and transformative approach to post-crisis recovery, contributing to more inclusive and sustainable community development. The study recommends strengthening institutional capacity, enhancing policy support, and expanding access to resources to maximize its impact. Future research is encouraged to explore comparative contexts and long-term outcomes to deepen understanding of its role in resilience building.